2012
DOI: 10.1111/j.1537-2995.2012.03940.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, incidence, and residual risks for transfusion‐transmitted human immunodeficiency virus Types 1 and 2 infection among Chinese blood donors

Abstract: Background There is little data on HIV prevalence, incidence or residual risks for transfusion transmitted HIV infection among Chinese blood donors. Methods Donations from five Chinese blood centers in 2008–2010 were screened using two rounds of ELISA testing for anti-HIV-1/2. A reactive result in either or both rounds led to Western Blot confirmatory testing. HIV prevalence and demographic correlates among first time donors, incidence rate and demographic correlates among repeat donors were examined. Weight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
41
2
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 21 publications
(27 reference statements)
3
41
2
1
Order By: Relevance
“…The medical history questionnaire comprises the screening fields mandated by the Chinese Ministry of Health [13]. Briefly, all donors must declare any history of sexually transmitted diseases or hepatitis, illegal drug use, or sex with multiple partners.…”
Section: Methodsmentioning
confidence: 99%
“…The medical history questionnaire comprises the screening fields mandated by the Chinese Ministry of Health [13]. Briefly, all donors must declare any history of sexually transmitted diseases or hepatitis, illegal drug use, or sex with multiple partners.…”
Section: Methodsmentioning
confidence: 99%
“…In areas with lower HIV prevalence such as Zhejiang and Gansu, HIV‐seropositive rates among voluntary unpaid donors are 0.002% to 0.003% . A recent study among 821,320 donations at five regional blood centers found HIV prevalence among voluntary donors to be 0.07% …”
Section: Blood Safetymentioning
confidence: 99%
“…The factors contributing to this high HCV RNA–positive rate among seronegative units could include false‐negative HCV antibody test results, false‐positive HCV RNA PCR results, and true window‐phase HCV infections. A study in five regional blood centers estimated the current HIV TTI residual risk to be 5.4 infections per million (0.00054%) whole blood donations . These findings suggest that there might be a relatively large number of TTI‐infected units that are not being detected by the current screening system at Chinese blood centers.…”
Section: Blood Safetymentioning
confidence: 99%
“…Ideally, the predonation health screening questionnaire should have deferred all donors who have had medical history, family history, or risk behaviors associated with infectious diseases including HIV infection. Yet, reports on the increasing serologic reactive rates for syphilis and HIV infections among Chinese blood donors have raised questions about the effectiveness of the current donor health screening questionnaire . Little is known about the major risk factors and the importance of such risk factors for HIV infection among Chinese blood donors.…”
mentioning
confidence: 99%
“…We conducted a multi–blood center survey study in four HIV high‐prevalence regions to explore the primary risk factors for HIV infection in Chinese blood donors and the relative importance of these risk factors. Based on 821,320 donations collected in 2008 to 2010 and Western blot confirmatory test results of anti‐HIV‐1/2 enzyme‐linked immunosorbent assay (ELISA) screen–reactive samples, the estimated mean HIV prevalence among blood donors in these regions was 66 (range, 2‐100) per 100,000 first‐time donors and the incidence among repeat donors was 9 (range, 1‐13) per 100,000 person‐years . The specific risks we examined included illegal drug use; hetero‐ and/or homosexual behavior; transfusion history; history of previous whole blood or plasma donation; self‐ and family history of hepatitis, HIV, and other infectious diseases; and medical injections and acupuncture, as well as having tattoo or body piercing and so forth as routes of transmission for HIV.…”
mentioning
confidence: 99%